Brain Changes Associated With Long-Term Ketamine Abuse, A Systematic Review - Strous, Jurriaan F. M.; Weeland, Cees J.; van der Draai, Femke A.; Daams, Joost G.; Denys, Damiaan; Lok, Anja; Schoevers, Robert A.; Figee, Martijn (Frontiers in Neuroanatomy, 2022)
Recently, the abuse of ketamine has soared. Therefore, it is of great importance to study its potential risks. The effects of prolonged ketamine on the brain can be observationally studied in chronic recreational users. We performed a systematic review of studies reporting functional and structural brain changes after repeated ketamine abuse. We searched the following electronic databases: Medline, Embase and PsycINFO We screened 11,438 records and 16 met inclusion criteria, totaling 440 chronic recreational ketamine users (2–9.7 years; mean use 2.4 g/day), 259 drug-free controls and 44 poly-drug controls. Long-term recreational ketamine use was associated with lower gray matter volume and less white matter integrity, lower functional thalamocortical and corticocortical connectivity. The observed differences in both structural and functional neuroanatomy between ketamine users and controls may explain some of its long-term cognitive and psychiatric side effects, such as memory impairment and executive functioning. Given the effect that long-term ketamine exposure may yield, an effort should be made to curb its abuse.